Factors Affecting the Ability of the Stroke Survivor to Drive Their Own Recovery outside of Therapy during Inpatient Stroke Rehabilitation - Xue Wen Eng; Sandra G. Brauer; Suzanne S. Kuys; Matthew Lord; Kathryn S. Hayward (Stroke Research and Treatment)
Aim. To explore factors affecting the ability of the stroke survivor to drive their own recovery outside of therapy during inpatient rehabilitation. Method. One-on-one, in-depth interviews with stroke survivors (n=7) and their main carer (n=6), along with two focus groups with clinical staff (n=20). Data was thematically analysed according to group. Results. Stroke survivors perceived “dealing with loss,” whilst concurrently “building motivation and hope” for recovery affected their ability to drive their own recovery outside of therapy. In addition, they reported a “lack of opportunities” outside of therapy, with subsequent time described as “dead and wasted.” Main carers perceived stroke survivors felt “out of control … at everyone’s mercy” and lacked knowledge of “what to do and why” outside of therapy. Clinical staff perceived the stroke survivor’s ability to drive their own recovery was limited by the lack of “another place to go” and the “passive rehab culture and environment.” Discussion. To enable the stroke survivor to drive their own recovery outside of therapy, there is a need to increase opportunities for practice and promote active engagement. Suggested strategies include building the stroke survivor’s motivation and knowledge, creating an enriched environment, and developing daily routines to provide structure outside of therapy time.